The Role of Jepuro Inter-Ethnic Cemeteries in Religious Moderation: Global Sociological and Anthropological Perspectives - Fathimatuz Zahra; Moch Nasrul Hakim; A.M. Wibowo; Dwi Istiyani (Historia Social y de la Educación)
Interethnic cemeteries, often overlooked by historians, possess great cultural and sociological value. This study analyses the Jepuro cemeteries in Juwana, Pati, highlighting their importance in the religious moderation of the region. These cemeteries reflect the community’s ability to manage ethnic and religious diversity with little conflict. The study addresses three key questions: the influence of interethnic funerals on the community’s philosophy and notion of religious moderation, and the impact of remains in the graves. Through a qualitative approach, observations, and interviews with residents, it is concluded that the cultural diversity brought by immigrants through the port of Tanjungpuro fostered religious moderation in the region. The variety of gravestones reflects a historical understanding of moderation being restored, and the interethnic burials show that religious moderation has been transmitted over generations. Preserving these cemeteries is not just important, it is essential, as they represent the community's multicultural legacy and its commitment to religious peace. It is suggested that local authorities protect these monuments and integrate their history into educational programs.